Winter distribution of toxic, potentially toxic phytoplankton, and shellfish toxins in fjords and channels of the Aysén region, Chile - Pizarro, Gemita; Paz, Beatriz; Alarcón, César; Toro, Carolina; Frangopulos Rivera, Maximo Jorge; Salgado, Pablo; Olave, Carlos; Zamora, Claudia; Pacheco, Hernán; Guzmán, Leonardo (My University, 2018)
Abstract The Aysén region (43°-47ºS) has been prone to intensive summer blooms of toxic microalgae and complex toxin profiles in the shellfish. However, their winter distribution, toxin profile, and resting cysts in sediments are poorly known. Frequently detected toxins are: Paralytic Shellfish Toxins (PST); lipophilic toxins, including Diarrheic Shellfish Toxins (DST), Amnesic Shellfish Toxin or Domoic Acid (DA). During a cruise, carried out in winter 2012, samples were collected at 24 stations for phytoplankton analysis and analysis of toxins in mollusks, and at 5 stations, additional samples were taken for toxin analysis in plankton and resting cysts in sediments. The results confirm the presence of microalgae associated with toxins in winter, and a higher sensitivity of the relative abundance (RA) than the cellular density, as a parameter of distribution of the microalgae. The maximum RA values were level 2 (low), for Alexandrium catenella and Protoceratium reticulatum; level 1 (rare) for Alexandrium ostenfeldii, Dinophysis acuminata and D. acuta; levels 3 (regular) and 4 (abundant) for Pseudo-nitzschia spp. seriata complex and Pseudo-nitzschia spp. delicatissima complex, respectively. Only PST in plankton and yessotoxins in mo llusks were detected, whereas cyst densities of A. catenella and P. reticulatum in sediments were 4 and 103 cysts mL-1 of wet sediment, respectively. The analyzed parameters showed a bigger inter-annual variability during the winter period, as it has been reported for the summer.
Keywords: pst; dst; domoic acid; lipophilic toxins; toxic phytoplankton; patagonian fjords